2001
DOI: 10.1080/10255840008908000
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Model of the Upper Limb Based on the Visible Human Male Dataset

Abstract: A mathematical model of the human upper limb was developed based on high-resolution medical images of the muscles and bones obtained from the Visible Human Male (VHM) project. Three-dimensional surfaces of the muscles and bones were reconstructed from Computed Tomography (CT) images and Color Cryosection images obtained from the VHM cadaver. Thirteen degrees of freedom were used to describe the orientations of seven bones in the model: clavicle, scapula, humerus, radius, ulna, carpal bones, and hand. All of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
209
1
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 219 publications
(221 citation statements)
references
References 48 publications
6
209
1
5
Order By: Relevance
“…With regard to the results, the values in Table II show that the average estimates of , and are consistent with physiological values as reported in [9,16], with for extensors the only overestimated parameter. This might be explained by considering that the total torque exerted during extension experiments was ascribed to ECRL only.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…With regard to the results, the values in Table II show that the average estimates of , and are consistent with physiological values as reported in [9,16], with for extensors the only overestimated parameter. This might be explained by considering that the total torque exerted during extension experiments was ascribed to ECRL only.…”
Section: Discussionsupporting
confidence: 71%
“…4A shows a shallower trend with regard to the flexor moment variability when compared to data from [16][17][18][19]. In the works from [16][17][18] flexor moment peaks were mainly located in the flexed region, while in Garner and Pandy [9] the highest peak was located at 0°. In the present study the highest values were found in extended positions as also reported in [19] and in [22].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A subject-specific musculoskeletal model was used to estimate strains during a fastball pitch performed by an MLB player (24). Muscle volumes within the player were obtained from 3D MR images (Siemens).…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that the Dickerson model is an implementation of the model developed by Hogfors and co-workers (Hogfors et al, 1987(Hogfors et al, ,1991(Hogfors et al, ,1995. For the other included models, moment arm data were extracted from published or dissertation data from the Favre model (Favre et al, 2005), Garner model (Garner and Pandy, 2001), and Newcastle model (Charlton, 2003); the availability of these models is not known.…”
Section: Methodsmentioning
confidence: 99%